U.S. Marshals [videorecording (DVD)] - Pantoliano, Joe; Downey, Robert, Jr., 1965-; Jones, Tommy Lee, 1946-; Snipes, Wesley; Baird, Stuart (Distributed by Warner Home Video, 2009)
U.S. Marshal Samuel Gerard is back with his team of marshals, assigned to track down Mark Sheridan, a murderer and robber. At the same time, Sheridan is out to find the truth himself while keeping one step ahead of Gerard.